Drug Related Problems (DRPs) pada pasien hipertensi rawat jalan di Puskesmas Ridge Kecamatan Distrik Samofa Kabupaten Biak Provinsi Papua Tahun 2025 - Bambang Hendrawan; Fitria Fitria; Syarifah Yanti Astryna; Nurhayati Nurhayati (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Hypertension is a chronic condition requiring long-term pharmacotherapy, which increases the risk of Drug-Related Problems (DRPs), particularly in outpatient settings. Limited data exist regarding DRPs in primary healthcare facilities in eastern Indonesia, especially Papua Province. Objective: This study aimed to identify and describe DRPs, including subtherapeutic dosage, supratherapeutic dosage, ineffective drug, inappropriate drug combination, and drug interactions, among hypertensive outpatients at Ridge Community Health Center, Samofa District, Biak Regency, Papua Province, in 2025. Methods: A non-experimental descriptive study with a retrospective design was conducted using medical records and prescription data from hypertensive outpatients. A total of 96 prescriptions were selected through simple random sampling from the January–May 2025 period. DRPs were evaluated based on the National Guidelines for Medical Services (PNPK) for Hypertension 2021, the British National Formulary (BNF), and the Drug Information Handbook, while drug interactions were assessed using Lexicomp® Drug Interactions and Medscape. Data were analyzed descriptively and presented as frequencies and percentages. Results: No DRPs were identified in the categories of subtherapeutic dosage, supratherapeutic dosage, or ineffective drug. Inappropriate drug combinations were observed in 15 patients (15.6%), while 81 patients (84.4%) had no such issues. Drug interactions were also identified in 15 patients (15.6%), involving amlodipine-simvastatin and candesartan-ibuprofen combinations. All cases of inappropriate drug combinations concurrently exhibited potential drug interactions. Conclusion: DRPs among hypertensive outpatients at Ridge Community Health Center were predominantly characterized by inappropriate drug combinations and drug interactions, while dosage-related problems were absent. These findings underscore the need for systematic prescription review and routine drug interaction screening in primary care settings to optimize antihypertensive therapy outcomes and ensure patient safety.